Real / Life : New British Art. - Roberts, James; Rose, Andrea; Fukuoka Art Museum, Fukuoka; Hiroshima City Museum of Contemporary Art, Hiroshima; Museum of Contemporary Art, Tokyo; Ashiya City Musuem of Art & History, Ashiya (Tochigi : Tochigi Prefectural Museum of Fine Arts, 1998)
Collishaw, Mat ; Doherty, Willie ; Floyer, Ceal ; Gallaccio, Anya ; Gordon, Douglas ; Hatoum, Mona ; Hume, Gary ; Lucas, Sarah ; Starr, Georgina ; Taylor-Wood, Sam ; Wearing, Gillian ; Whiteread, Rachel
biografie, bibliografie
Tochigi Prefectural Museum of Fine Arts, Tochigi, 12 April - 31 May 1998 ; Fukuoka Art Museum, Fukuoka, 27 June - 26 July, 1998 ; Hiroshima City Museum of Contemporary Art, Hiroshima, 12 August - 25 September 1998 ; Museum of Contemporary Art, Tokyo, 10 October - 13 December 1998 ; Ashiya City Musuem of Art & History, Ashiya, 15 January - 14 March 1999
English-Japanese
kunstcatalogus